Evaluation of Serum Magnesium Level in Preeclampsia (Bangladesh Journal of Medical Biochemistry, 2018)
Preeclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Reduced serum magnesium level is found to be associated with elevated blood pressure in preeclampsia. The purpose of this cross-sectional study is to evaluate the serum magnesium level in preeclamptic women. For this study 50 preeclamptic patients, with age range 20 to 40 years having gestational age range from 20 to 40 weeks and 50 age and gestational age matched normotensive pregnant women having no proteinuria were enrolled. Serum magnesium was measured by colorimetric method. The mean(±SD) age and mean(±SD) gestational age of preeclampsia was not significantly different from those of normotensive pregnant women (p=0.203 and p=0.251 respectively). The mean(±SD) body mass index of the preeclamptic patients was significantly higher compared to that of normotensive pregnant women (p